COMPARATIVE ANALYSIS OF GOOGLE SCHOLAR, SCOPUS, AND WEB OF SCIENCE IN MODERN ACADEMIC RESEARCH - Rustamova Adash Eshankulovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Academic databases and citation indexing systems play a fundamental role in modern scientific communication, research evaluation, and knowledge dissemination. Among the most widely used scholarly databases are Google Scholar, Scopus, and Web of Science, each offering unique features, coverage, citation metrics, and analytical tools for researchers and academic institutions. These databases significantly influence literature review processes, bibliometric analysis, university rankings, and scholarly visibility. This article provides a comparative analysis of Google Scholar, Scopus, and Web of Science in terms of content coverage, indexing standards, citation analysis, accessibility, research evaluation, and usability. The study also examines the strengths and limitations of each platform in supporting academic research and scientific collaboration. Furthermore, the article discusses the impact of digital transformation and globalization on scholarly databases and citation systems. The findings indicate that while Scopus and Web of Science maintain stricter quality control and advanced analytical tools, Google Scholar offers broader accessibility and extensive coverage of academic materials. The article concludes that understanding the differences among these databases is essential for effective research management, publication strategy, and academic evaluation.
Keywords: Keywords: Google Scholar, Scopus, Web of Science, citation databases, bibliometric analysis